Editorial - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Finally, the JIFAM, Volume 2, Issue 2, September 2020 can be published, and it consists of 7 papers. This year, the JIFAM is still published bi-annualy in March and September and is set to consist of 5-7 papers. Indonesia has a program to move its capital from Jakarta to East Kalimantan. It is a huge program and very rich of IFAM problems. Therefore, this is an excellent case study for developing the knowledge and science of IFAM. Started from JIFAM 2(1), JIFAM publishes paper related to capital relocation cases. JIFAM invites authors from all over the world to submit papers related to capital relocation matter, to enrichi and to deepen the discussion. The JIFAM Editorial Team express their gratitude to the authors who already submitted their papers for this second issue of the second volume.